Environmental licensing in secondary sloping wooden enterprises in the State of Acre in the years 2010-2014 - Freitas, Marcelo Ferreira de; Freitas, Ívina Zuleide Gonçalves de Sousa (Seven Editora, 2024)
Every year, forest-based activities have been expanding in the State of Acre and, to ensure the environmental sustainability of ecosystems, several protection instruments have been created, including Environmental Licensing, to regulate activities and enterprises that use natural resources in a way that does not cause or minimize their degradation. In this sense, the present study aimed to analyze the licensing process in the State of Acre between 2010-14, specifically, regarding the Forest Industry sector in the activities of secondary harvesting and wood processing. For the methodology, the descriptive method was used, based on the collection of data from the Annual Management Reports of DIF/Imac, regarding the following: (a) evolution of the number of licensed secondary development projects; (b) evolution of the areas covered by licensed secondary development projects and (c) annual changes in the number and area covered by non-licensed projects. The results were: (a) significant protocol of environmental licensing processes in the simplified modality; (b) only in 10 municipalities of the State, there was a request for licensing for secondary development in the normal modality; (c) Rio Branco and Sena Madureira were the municipalities where there were more restrictions on licensing in both modalities. The study showed that the licensing presented a positive balance, as the total number of licensed enterprises in the evaluated period exceeded the number of non-licensed, reflecting on the development of the region’s economy, where companies left illegality and began to contribute directly to the growth of the State. DOI:https://doi.org/10.56238/sevened2024.007-044